Risk factors for local recurrence of large, flat colorectal polyps after endoscopic mucosal resection - Zhan, Tianzuo; Hahn, Felix; Hauf, Corinna; Betge, Johannes; Ebert, Matthias; Belle, Sebastian (Digestion, 2016)
Aims: Removal of large, flat colorectal polyps by endoscopic mucosal resection (EMR) is effective, but local recurrences occur regularly. This study investigated risk factors for local recurrence. Method: Cases of EMR of flat colorectal polyps ≥20 mm at an academic center from 2004 to 2011 were retrospectively analyzed for polyp features, resection technique, complications and local recurrences. Behavioral risk factors were retrospectively determined by self-administered questionnaires. Results: Data were collected for 129 patients (57.3% male, mean age at time of EMR: 65.0 years). Mean polyp size was 37.2 mm. Polyps were mostly adenoma with low-grade dysplasia (58.1%) and predominantly located in the right colon (62%). En bloc resection was performed in 31.8%. The median follow-up time was 40 months. Local recurrence occurred in 26.3% of patients, with 87% being recurrence-free after 1 year (95% CI 81-93%). A history of smoking was reported by 51.6% of patients and 88.4% reported regular alcohol consumption. Univariate analysis showed that polyp size and piecemeal resection were associated with risk of local recurrence. In multivariate analysis, only polyp size was predictive for local recurrence. No association was found for behavioral risk factors. Conclusion: Polyp size is the main predictor of local recurrence after EMR of large, flat colorectal polyps.